Scenario planning development for a multi-national printing ink company facing digital disruption in Indonesian print media industry: DOI 10.14622/JPMTR-2101 - Suhariyono, Bambang Catur; Sunitiyoso, Yos; Yuniarto, Ahmad (Journal of Print and Media Technology Research, 2021)
The rapid development of digital technology gives disruptive influences on the value of goods or services. New media communication technology offers media convergence that provides accessible speed, flexibility, and updated information. The existence of print media has become less common in the market. This affects all print media industry suppliers, including a printing ink company. The company will get decreasing revenue, especially if most of its current revenue comes from print media ink sales. Digital disruption is a certain thing, but uncertainty in print media arises because of the pros and cons of using digital devices for children’s education, the freedom of online journalism that provides doubtful information, and the emergence of community media. The printing ink company also needs to prepare itself by making a strategy for the future that is full of those uncertainties. In this case, scenario planning can help the company to manage the uncertain future so that they can quickly adapt to the changes or the critical situations in the future and manage the complexity of turbulence, uncertainty, novelty, and ambiguity, that happen in the current Covid-19 pandemic. The key focal issue of this research is how digital disruption in the print media industry in Indonesia will affect a multi-national printing ink company over the next five years. The research involved experts from a multi-national printing ink company, a magazine publisher, a university, a digital printing consultant, a business consultant, and a disrupted public transport provider. Through intensive focus group discussion applying iterative reframing and re-perception, many driving forces were identified, two critical uncertainties were defined, and a scenario framework was created. The four scenarios came up as the result of the interaction between limited or widely available global ink supply and changes in people’s behavior from conventional to digital media. These scenarios describe future challenges for the print media industry in Indonesia that are very dynamic. The company must be able to respond to emerging scenarios and adapt the strategies accordingly.